THE EFFECT OF PRODUCTION COST AND OPERATIONAL COST TO NET PROFIT (STUDI IN FOOD AND BEVERAGE SUB SECTOR COMPANIES LISTED AND INDONESIAN STOCK EXCANGE IN 2019-2023) - Siagian, Frisca; Hardiana R, Dicky; Dameria N, Rina; Setiyo Dewi, Diana (Jurnal Akuntansi dan Perpajakan Jayakarta, 2025)
The study aims to determine the effect of production costs and operational costs to net profit. The type of data used in this study is secondary data in the form of company annual financial reports. The research population is the food and beverage sub sector companies listed on the Indonesia Stock Exchange in 2019-2023. Sampling was carried out by purposive sampling method with a total sample of 75 samples. The analytical technique used is Multiple Linear Regression using the SPSS program. The results show that the production costs variable do not have a significant effect on net profit, while the operational costs variable have a positive significant effect on net profit, and the two variables production costs and operational costs have a simultaneous influence on net profit. The limitation of this study is that it only uses a sample of food and beverage sub sector companies that are listed on the Indonesia Stock Exchange in 2019-2023